Women on men's sexual health and sexually transmitted infection testing: a gender relations analysis. Issue 1 (12th April 2012) - Oliffe, John L.; Chabot, Cathy; Knight, Rod; Davis, Wendy; Bungay, Vicky; Shoveller, Jean A.
Abstract Sexual health and sexually transmitted infection (STI) testing is typically portrayed as a women's issue amid men's estrangement from healthcare services. While the underreporting of men's STIs has been linked to masculinities, little is known about how women interpret and respond to heterosexual men's sexual health practices. The findings drawn from this qualitative study of 34 young women reveal how femininities can be complicit in sustaining, as well as being critical of and disrupting masculine discourses that affirm sexual pleasure and resistance to health help‐seeking as men's patriarchal privileges. Our analysis revealed three patterns: looking after the man's libido refers to women's emphasised femininity whereby the man's preference for unprotected sex and reticence to be tested for STIs was accommodated. Negotiating the stronger sex refers to ambivalent femininities, in which participants strategically resist, cooperate and comply with men's sexual health practices. Rejecting the patriarchal double standard that celebrates men as 'studs' and subordinates women as 'sluts' for embodying similar sexual practices reflects protest femininities. Overall, the findings reveal that conventional heterosexual gender relations, in which hegemonic masculinity is accommodated by women who align to emphasised femininity, continues to direct many participants' expectations around men's sexual health and STI testing.